Triceratops and other horned dinosaurs the need-to-know facts - Clay, Kathryn (North Mankato, MN Capstone Press, 2016)
Full-color images and simple text introduce young readers to different horned dinosaurs, including their physical characteristics, habitats, and diets"-
The World Around us
a gift from book africa
1 2 13
Keywords: Ceratopsians -- Juvenile literature; Dinosaurs -- Juvenile literature; Triceratops -- Juvenile literature